Risk Factors Associated with Hypertension Among Outpatients at Sukarame Primary Health Center, Bandar Lampung, Indonesia - Diah Adeli Emilda; Fika Khikma Fiana; Cucu Herawati (Media of Health Research, 2026)
Hypertension remains one of the most significant public health challenges worldwide and contributes substantially to cardiovascular morbidity and mortality, particularly in low- and middle-income countries such as Indonesia. Previous studies have demonstrated that hypertension is influenced by a complex interaction of demographic, behavioral, and metabolic factors; however, evidence focusing on outpatients at primary health care facilities is still limited. This study aims to analyze risk factors associated with hypertension among outpatients at Sukarame Primary Health Center, Bandar Lampung, Indonesia. A cross-sectional analytical design was employed using secondary and primary data collected from adult outpatients. Sociodemographic characteristics, lifestyle factors, and clinical conditions were analyzed using descriptive and inferential statistics. The results indicate that age, obesity, physical inactivity, smoking habits, and high salt consumption are significantly associated with hypertension. Obesity and low physical activity emerged as the most dominant risk factors. These findings are consistent with previous national and regional studies conducted in various Indonesian settings. The study highlights the importance of strengthening preventive strategies at the primary health care level through lifestyle modification programs, routine screening, and patient education. In conclusion, addressing modifiable risk factors remains a key strategy to reduce the burden of hypertension among outpatients in primary health centers.